Fall-Planted Cover Crops for Weed Suppression in Western Kansas - S. Dhanda; V. Kumar; A. K. Obour; A. Dille; J. D. Holman (Kansas Agricultural Experiment Station Research Reports, 2022)
The widespread evolution of herbicide-resistant (HR) kochia and Palmer amaranth warrants the use of alternative ecological-based strategies for weed management in no-tillage (NT) dryland cropping systems in western Kansas. A field study was established in the fall of 2020 at Kansas State University Agricultural Research Center near Hays, KS, to determine the impact of fall-planted cover crop (CC) mixture on 1) kochia and Palmer amaranth suppression (density and biomass reduction), and 2) Palmer amaranth emergence dynamics in subsequent grain sorghum. A CC mixture of winter triticale, winter pea, radish, and rapeseed was planted in wheat stubble in the fall of 2020. The CC mixture was terminated at triticale heading stage on May 26, 2021 by using 1) Roundup PowerMax (glyphosate) at 32 fl oz/a, and 2) Roundup PowerMax at 32 fl oz/a + Degree Xtra (premix of acetochlor + atrazine) at 2.2 quart/a. A chemical fallow treatment (without CC) was included for comparison. The study site was planted with grain sorghum hybrid ‘DKS 38-16’ on June 10, 2021. The CC mixture produced an average of 1360 lb/a aboveground biomass at the time of termination. The CC terminated with Roundup PowerMax + Degree Xtra had 98 and 95% less total weed density at 0 and 30 days after termination (DAT), respectively, compared to chemical fallow. No difference in weed density was observed at later evaluations. At grain sorghum harvest, CC terminated with Roundup PowerMax and Roundup PowerMax + Degree Xtra reduced total weed biomass by 61% and 73%, respectively, compared to chemical fallow. The time taken to reach 10, 50, and 90% cumulative emergence of Palmer amaranth was delayed by 9, 15, and 21 days, respectively, in CC terminated with Roundup PowerMax and 11, 39, and 128 days, respectively, in CC terminated with Roundup PowerMax + Degree Xtra when compared with chemical fallow. Grain sorghum yield did not differ between CC and chemical fallow treatments. These results suggest that a fall-planted CC mixture can play an important role for kochia and Palmer amaranth suppression in NT dryland crop production in western Kansas.
Keywords: cover crop; dry land; kochia; Palmer amaranth; suppression